Digital Compositing Dalam Film Animasi 3 Dimensi - Rahmad, Cito Yasuki Yasuki (Capture : Jurnal Seni Media Rekam, 2011)
Animation is a technique mostly used in the film world. Nowadays it is growing intechnical animation creation. Animation has evolved from 2D animation to the nextstage in the new form, more realistic and interesting, that is the 3D animation. With thedevelopment of existing technology, the 3D animation is more amazing for the audience,especially 3D animation combined with real action (live action). With the digitalcompositing, the result of a combination of 3D and real action to make the film seemmore alive, because the animation is really close to the original in real life.